Sounds of tohi : Cherokee health and well-being in Southern Appalachia - Lefler, Lisa J.; Belt, Thomas N. (The University of Alabama Press, 2022)
"This project is the result of almost two decades of work by medical anthropologist Lisa J. Lefler and Cherokee Elder and traditionalist Thomas N. Belt. It is a "dialogue" of their interest and application of traditional indigenous knowledge and the importance of place for two people from cultures and histories that intersect in the mountains of southern Appalachia. They have worked to decolonize thinking about health, well-being, and environmental issues through the language and experiences of people whose identity is inextricably linked to the mountains and landscape of western North Carolina. In this book, they discuss the Cherokee (Kituwah) concept of health, tohi, along with other critical cultural concepts that explain the science of relationships with this world, with the spirit world, and with people. Tohi infers a more pervasive understanding that the relationships in life are all balanced and moving forward in a good way. They discuss the importance of matrilineality, particularly in light of community healing, the epistemologies of Cherokee cosmography, and decolonizing counseling approaches. They hope to offer a different way of approaching the issues that face this country in this time of difficulty and division. They share their urgency to take action against the wholesale exploitation of public lands and shared environment, to work to perpetuate tribal languages, to preserve the science that can make a difference in how people treat one another, and to create more forums that are inclusive of Native and marginalized voices and that promote respect and appreciation of one another and protection of sacred places. Throughout, they rely on the preservation of traditional knowledge, or Native science, via the language to provide insight as to why people should recognize a connection to the land. These notions are supported through insight from thinkers representing a variety of disciplines"--